2022
DOI: 10.3389/fpls.2022.841161
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Bioinformatics Analysis of GhArfGAP in Cotton (Gossypium hirsutum) Boll Abscission Layer With Ethylene Treatment

Abstract: With the continuous growth of the human population, the demand for fiber is also rising sharply. As one of the main fiber plants available globally, cotton fiber yield (Gossypium hirsutum) is affected by boll abscission, which is related to the formation of the abscission layer. Therefore, we explored the formation of the abscission layer in cotton. The formation of the abscission layer in the cotton boll stalk was promoted by exogenous ethylene. It was found that both the number of the Golgi apparatus and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…The formation of the abscission layer is promoted by ethylene in both mango [ 49 ] and cotton [ 50 ]. In accordance with these findings, in another study, the abscission layer started to form at 12 h after a treatment with 400 mg/L ethylene treatment of cotton bolls [ 51 ]. However, some studies have shown that although ethylene can accelerate abscission under many conditions, it is not essential [ 52 ].…”
Section: Discussionsupporting
confidence: 69%
“…The formation of the abscission layer is promoted by ethylene in both mango [ 49 ] and cotton [ 50 ]. In accordance with these findings, in another study, the abscission layer started to form at 12 h after a treatment with 400 mg/L ethylene treatment of cotton bolls [ 51 ]. However, some studies have shown that although ethylene can accelerate abscission under many conditions, it is not essential [ 52 ].…”
Section: Discussionsupporting
confidence: 69%